The Roles and Responsibilities of Land Deed Officials in the Registration of Transfer of Land Rights as a Result of Sale and Purchase - Ahmad Zahrial, Fadhil; Hafidz, Jawade (Master of Notarial Law, Faculty of Law, Sultan Agung Islamic University, 2023)
. This study aims to identify and explain the roles and responsibilities of the PPAT in registering the transfer of land rights as a result of buying and selling in Blora Regency, and to identify and explain the obstacles encountered in carrying out the registration of transfer of land rights as a result of buying and selling in Blora Regency. as well as the solution. The method used is a juridical-sociological approach, with descriptive analytical research specifications. The types of research data include primary legal materials, secondary legal materials, and tertiary legal materials. The analytical method used in this study is a qualitative analysis method. Based on the results of the study it was concluded that the responsibilities of the Land Deed Making Officer (PPAT), namely in making and issuing Deeds of Transfer of Land Rights, must comply with the provisions of the applicable regulations. Obstacles in registering the transfer of land rights include incomplete paperwork, disputes with neighbours, lands for sale and purchase that have not been registered, the community is reluctant to certify the transfer of rights over their land. The solution to overcome the obstacles that occur during the implementation of the transfer of land rights in Blora Regency. Explains that, checks and examines the files, records them in the filling form, gives a receipt for the application files, and gives the applicant to complete the files through a notification letter. At the time of measurement there is a difference in the size of the land object in the certificate, it is better to report back to the BPN for re-checking. The land office organizes a mass certification program, especially for the less fortunate, so that the need for certificates can be met in a fair manner. Keywords: Land; Rights; Transfer.